The Influence of Motivation on the Quality of the Leader – Follower Relationship - Simic, Jelena; Tamara Kezic; Marija Runic Ristic (European Journal of Social Science Education and Research, 2018)
The subject of this research is the connection of the motivational structure with the quality of the leader –follower relationship. The aim is to determine the ways to improve the quality of the leader – fololower relationship which will consequently enhance the productivity and the satisfaction of employees. The research results have shown that the motivational factors, such as reward systems, good interpersonal relationships, career development possibilities and good team spirit, are significantly statistically associated with the leader – follower relationship. The sample includes 300 respondents with different educational and professional profiles, employed in various public and private sectors in Serbia. An interdisciplinary approach has been used in this paper, and the data have been processed by SPSS statistical analysis. Based on this research, we may conclude that the strategy of motivation throughout an organization is necessary. It should integrate motivational actions into several segments: the development of the importance of work, the awareness of employees’ personal values, good interpersonal relationships and the atmosphere of team work.